2002
DOI: 10.1038/sj.onc.1205116
|View full text |Cite
|
Sign up to set email alerts
|

The cancer growth suppressing gene mda-7 induces apoptosis selectively in human melanoma cells

Abstract: Human melanoma cells growth arrest irreversibly, lose tumorigenic potential and terminally di erentiate after treatment with a combination of ®broblast interferon (IFN-b) and the protein kinase C activator mezerein (MEZ). Applying subtraction hybridization to this model di erentiation system permitted cloning of melanoma di erentiation associated gene-7, mda-7. Expression of mda-7 inversely correlates with melanoma development and progression, with elevated expression in normal melanocytes and nevi and increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
258
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(280 citation statements)
references
References 45 publications
22
258
0
Order By: Relevance
“…9 Ectopic expression of MDA-7 using a replication-incompetent adenovirus construct (Ad.MDA-7) induced growth suppression and apoptosis in a number of human melanoma cell lines without the induction of terminal differentiation. 16 Similar effects also have been observed in a variety of other human cancer derived cell lines, including glioblastoma multiform, osteosarcoma, and breast, cervix, colon, lung, nasopharynx and prostate carcinomas, but not in any normal cells. 17,18 However, most of these studies were conducted before MDA-7 was shown to be a secreted cytokine, and the antitumor effect described in these studies was thought to result from intracellular, rather than secreted MDA-7.…”
Section: Introductionsupporting
confidence: 59%
“…9 Ectopic expression of MDA-7 using a replication-incompetent adenovirus construct (Ad.MDA-7) induced growth suppression and apoptosis in a number of human melanoma cell lines without the induction of terminal differentiation. 16 Similar effects also have been observed in a variety of other human cancer derived cell lines, including glioblastoma multiform, osteosarcoma, and breast, cervix, colon, lung, nasopharynx and prostate carcinomas, but not in any normal cells. 17,18 However, most of these studies were conducted before MDA-7 was shown to be a secreted cytokine, and the antitumor effect described in these studies was thought to result from intracellular, rather than secreted MDA-7.…”
Section: Introductionsupporting
confidence: 59%
“…Differences in tumor size were analyzed for significance by the Student's t-test. Enhanced in vitro growth inhibitory and cytotoxic activity of Ad-mda7 and Herceptin in Her-2 þ breast cancer cells The antiproliferative effects of Ad-mda7 in various cancer cell types have been demonstrated in previous studies; [16][17][18][19][20][21][22][24][25][26][27][28][29][30][31][32][33][34]36 and the relevance of these findings to the clinical setting is supported by in vivo lung and breast xenograft models. 17,21 To corroborate that the Her-2 receptors expressed by the breast cancer cells are functional, we evaluated cell death in MDA-MB-453 and MCF-7 lines treated with increasing amounts of Herceptin (0-100 mg/ ml).…”
Section: Discussionmentioning
confidence: 80%
“…[18][19][20][21][22][23]38 It is now known that mda-7 activates various signaling pathways in a cell-type-specific manner, and that these pathways ultimately converge on mitochondrial destruction and induction of apoptosis. 21,22,[24][25][26][27][28][29][30] However, in spite of its clear tumor-suppressive effects, the mechanisms by which Ad-mda7 induces cytotoxicity have not been fully characterized. Our group has previously demonstrated that Ad-mda7, as a single agent therapy, induces apoptosis and inhibits growth in pancreatic, lung and breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…26 Caspase 3/7 activities were measured using the Caspases-Glo 3/7 Assay Kit (Promega, Madison, MI) according to the manufacturer's instructions. For trypan blue cell death assay, cells were harvested by treatment with 0.05% trypsin/0.53 mM EDTA (ethylenediaminetetraacetic acid).…”
Section: Methodsmentioning
confidence: 99%
“…26 Briefly, cells were incubated with mouse monoclonal anti-CAR antibody for 1 h at 37 1C (1:1000 dilution; Millipore, Billerica, MA), washed, exposed to fluorescein isothiocyanate-conjugated anti-mouse immunoglobulins (1:1000 dilution; Sigma, St Louis, MO) for 1 h at 37 1C in the dark, washed again and analyzed on a FACSCalibur using CellQuest Pro version 5.2 (BD Biosciences, San Jose, CA). Unstained cells, cells stained with secondary antibody only and cells incubated with isotype control primary antibody, followed by secondary antibody, were used as controls.…”
Section: Methodsmentioning
confidence: 99%